A COMPARATIVE PRAGMATIC ANALYSIS OF SPEECH ACTS OF PERSUASION AND SUGGESTION IN RUSSIAN, CHINESE, AND UZBEK LINGUISTICS (American Journal of Pedagogical and Educational Research, 2026)
This article examines theoretical and applied studies of speech acts of persuasion and suggestion in Russian, Chinese, and Uzbek linguistics. It analyzes major approaches to interpreting these communicative phenomena within pragmatics, cognitive linguistics, and linguocultural studies. Special attention is paid to cross-cultural differences in the realization of persuasion and suggestion strategies. The findings demonstrate that while these speech acts share universal features, their linguistic representation and pragmatic mechanisms vary significantly depending on the cultural context.